Influence of Sowing Dates on the Phenological Development, Growth and Yield Of White Maize Genotypes (Bangladesh Agronomy Journal, 2021)
The experiment was conducted at the Sher-e-Bangla Agricultural University (90o22 E, 23o 41 N), Dhaka, Bangladesh in  Rabi (winter) season of 2017-2018 to study the effects of sowing date on  growth and  yield of four white maize genotypes, viz.  PSC-121, Yangnuo-7, Yungnuo-30 and Changnuo-6. Sowing dates were November 26, December 11, and December 26. Data were collected on different phenological growth stages, dry matter, physiological attributes, yield, and yield attributes. A delay in sowing date delayed the time required for seedling emergence, to reach the 6-leaf collar, maturity stage, and also reduced yield. The planting of PSC-121 in November 26 gave the highest dry matter plant-1, the number of grains cob-1, and 100- grain weight that resulted in the highest grain yield (11.65 t/ha) of the genotype.Bangladesh Agron. J. 2021, 24(1): 57-70